2021
DOI: 10.1073/pnas.2020997118
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear envelope budding is a response to cellular stress

Abstract: Nuclear envelope budding (NEB) is a recently discovered alternative pathway for nucleocytoplasmic communication distinct from the movement of material through the nuclear pore complex. Through quantitative electron microscopy and tomography, we demonstrate how NEB is evolutionarily conserved from early protists to human cells. In the yeast Saccharomyces cerevisiae, NEB events occur with higher frequency during heat shock, upon exposure to arsenite or hydrogen peroxide, and when the proteasome is inhibited. Yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 109 publications
2
41
0
Order By: Relevance
“…Lastly, the removal of INM contents through the proposed mechanism evokes comparisons to the nuclear-to-cytosolic translocation of so-called “mega” RNPs in some Drosophila neurons that proceeds through a vesicular intermediate in the NE lumen ( Speese et al, 2012 ). Similar structures have been observed in yeast upon inhibiting nuclear export ( Ding et al, 2017 Preprint ) and as part of a stress response ( Panagaki et al, 2021 ). Thus, we anticipate that the removal of intranuclear contents through the NE lumen will prove to be a generalizable principle of protein, and perhaps RNA, quality control that will be relevant beyond the yeast system and that has, in fact, already been hypothesized ( Rose and Schlieker, 2012 ).…”
Section: Discussionsupporting
confidence: 67%
“…Lastly, the removal of INM contents through the proposed mechanism evokes comparisons to the nuclear-to-cytosolic translocation of so-called “mega” RNPs in some Drosophila neurons that proceeds through a vesicular intermediate in the NE lumen ( Speese et al, 2012 ). Similar structures have been observed in yeast upon inhibiting nuclear export ( Ding et al, 2017 Preprint ) and as part of a stress response ( Panagaki et al, 2021 ). Thus, we anticipate that the removal of intranuclear contents through the NE lumen will prove to be a generalizable principle of protein, and perhaps RNA, quality control that will be relevant beyond the yeast system and that has, in fact, already been hypothesized ( Rose and Schlieker, 2012 ).…”
Section: Discussionsupporting
confidence: 67%
“…1 B, see 5 and 45 min). Electron-dense content, which has also been shown to be protein aggregates in the case of the nucleus ( Panagaki et al, 2021 ), was observed in both the nucleus and mitochondria ( Fig. 1 B, see 15, 30, 45 and 90 min).…”
Section: Resultsmentioning
confidence: 55%
“…In order to facilitate the transport of macromolecules such as proteins and RNAs between the cytoplasm and the nucleus, the nuclear membrane maintains some pores that allow the passage of hydrophilic molecules smaller than 39 nm ( Panagaki et al, 2021 ). Theoretically, nanodrugs with dimensions smaller than 39 nm and hydrophilicity have the potential for passive nuclear targeting ( Fu et al, 2020 ).…”
Section: Passive Nucleus-targeting Nanodrugsmentioning
confidence: 99%